Communication Strategies Used by EFL Learners in Task-Based English Debate - Novia Rina Saidah; Ahmad Munir; Syafi’ul Anam (Linguistic, English Education and Art (LEEA) Journal, 2020)
This research aims to describe the use of communication strategies in an EFL classroom during the completion of task-based debate activity. This research was conducted in an English course located in Sidoarjo. The subject of this study are 10 EFL intermediate level students. In line with that reason, this research is a qualitative study since it focuses on the depth of the comprehension of the communication strategies data rather than computing it. For obtaining the data, the researcher do observation and records learners’ verbal and non-verbal behaviour based on Dornyei (1995) taxonomy of communication strategies during the debate activity. The result showed that all taxonomies by Dornyei are used by the subjects i.e avoidance strategies, achievement strategies, and stalling strategies in the debate. There are various reason for leaners to choose those strategies to overcome their communication breakdowns during the short-time debate between speakers such as because it’s time-efficient, less confusing, and sound trustworthy to lengthen their time to think, keep the communication channel at hand, and keep up the discourse at the moment when learners face the difficulties. As the conclusion, English debate activity is considered as one of the task that promotes students-centered learning in a TBLT class, provides opportunities for students to speak Engish, and challenge students to use their language sources to strengthen their arguments. In the debate, learners mostly applied stalling strategies such as fillers since is considered very easy and quick for learners to use when they encounter problems such as nervous, lack of vocab, and lack of grammar structure in the English debate activities. Keywords: Communication strategies, task-based learning, English debate.